Refrigerator standards and their impact on United States society. (28th April 2014) - Mapp, James; Reed, John H.
This paper addresses criticisms of US Federal appliance efficiency standards and whether or how the imposition of efficiency standards on household refrigerators and freezers in the US affects prices, supply, and various other attributes. The study is based on historical data about changes in standards for household refrigerators along with data about the size, styles, energy consumption, reductions in emissions, and the costs of refrigerators from 1940 to the present. Changes in standards are alleged to disrupt markets, which left to their own devices would optimise cost, efficiency, consumer choice, and reliability. This paper shows that standards have contributed to an overall reduction in unit energy consumption and CO2 emissions at the aggregate level and have reduced household costs for energy in constant 2011 US dollars. The data disprove critics' arguments of that standards who charge that the imposition of federal energy efficiency standards increase the cost of equipment for end users and limit availability.